SEPATAGUNG, INOVASI ALAT TANAM JAGUNG TERINTEGRASI DENGAN SEPATU KERJA PETANI - Ramdhan, Muhamad Shopia; Wicaksana, Bayu; Mardiana, Via; Faizal, Yusuf; ATD, Nurmagfiroh (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Corn ( Zea Mays L ) is the main food source of the world after rice and wheat. The demand for these commodities experienced thus increasing production of maize to the attention of many people. In Indonesia, the planting of the seed corn is still done traditionally caused due to mismatch condition of land with modern technology that has been made, besides the price factor for a mechanical corn cropping tool less attractive to farmers. So farmers still use traditional cropping tool which impact on the length of time required when planting. Sepatagung present provide appropriate solutions. Corn planting tool in the form of semi-mechanical drill is suitable for use by Indonesian farmers because agriculture in accordance with Indonesian culture, in addition to a more ergonomic, use sepatagung also has a working capacity which is almost equal to the mechanical planting equipment. The method used is to make a direct cropping tool that has been integrated with the shoes and make modifications to the shoe. The results achieved are generated mechanical spring corn planting tool that has a great working capacity with affordable price, easy operated and more ergonomic.Keyword : SEPATAGUNG, Zea mays L, Planter, Semi-mechanical, Tugal